Mathematics' Self-Efficacy and Peer Relation as a Predictor of Mathematics Achievement - Haq, Aniq Hudiyah Bil; Alsa, Asmadi (Universitas Muhammadiyah Surakarta, 2015)
Well-educated human resources will enable them to have the necessary competence to compete in this modern world since education and achievement remain an important standard for knowing their resourceness. This research is based on less number of Mathematics achievements of Senior High School Students in Indonesia. At the same time, mathematics is important subject in the development of communication and information technology. Therefore, this research aims to analyze and investigate Mathematics achievement on Senior High School students, which are observed based on Mathematics self-efficacy and peer relationship. This research is conducted by employing quantitative approach with regression analysis. Subjects used in this research are 143 students of Senior High School in Surakarta, who are measured for their Mathematics achievements by using cognitive final marks on report of odd semester of academic year 2013/2014. The variables of Mathematics selfefficacy and peer relationship are measured by using scales. Based on data analysis results, the conclusion obtained states that both Mathematics self-efficacy and peer relationship can predict Mathematics achievement.